Structure and factorial invariance of the Grit-Original scale and convergent validity of the network with job satisfaction and happiness - Ramos-Vera, Cristian; Soza-Herrera, Juan José; Quispe-Callo, Gleni; Serpa-Barrientos, Antonio; Calizaya-Milla, Yaquelin E.; Saintila, Jacksaint (Frontiers in Psychology, 2023)
Background The concept of Grit refers to a person’s ability to maintain perseverance and passion in the pursuit of long-term objectives. However, research on the applicability of the Grit-Original scale (Grit-O) in the Latin American context is limited. Objective This instrumental design study aimed to analyze the structure of this scale and its factorial invariance in relation to gender, as well as to examine its convergent validity with job satisfaction and happiness. Methods A sample of 364 Peruvian workers that were selected through non-probabilistic convenience sampling in 2021. Results The results of the confirmatory factor analysis showed that the two-dimensional structure of 12 items presented adequate goodness-of-fit indices. Additionally, the instrument is invariant between men and women. Likewise, the convergent relationship between the Grit scale, job satisfaction, and happiness variables was confirmed, which supports the validity of the instrument in the study context. Conclusion The findings of the study confirm that the GRIT-O is a measure with adequate psychometric properties in the Peruvian context.